Un quartier à soi : Demolició, le beau Raval de Virginie Manuel - Sonia Kerfa (Catalonia)
The southern part of El Raval, former Barcelona’s Barrio Chino, is intrinsically linked, in the city's imagination, to the world of an eternal lumpenproletariat, bound to a district of infinite possibilities, open both to the bourgeois canaille and the junky. The gentrification process which began in the late 90's has changed little in the uses of El Raval but it's population, very modest, has been deeply affected, as well as the urban pattern. The demolition of part of this district is the subject of a super 8 short film directed by Virginie Manuel, trained as an architect and local resident of a district of which she has observed the violent metamorphosis, as an artist. The brutality of the transformation pushed her to leave a record of the event she will film during more than two years (end of 1996 - 1999). Demolició reports this aesthetic and emotional relationship with the programmed ruin and with the construction workers who are transfigured by the cineast's camera. Carmen Amaya's daring "taconeo" brings fierce power to the film, which tells the obstinacy of a popular world, the disappearance of which should not be allowed.